Isolated sixth cranial nerve palsy as the first manifestation of pre-eclampsia with twin pregnancy-case report and review of literature - Ramnani, Vinita; Samadhiya, Richa; Mishra, Devanshi; Trivedi, Divya; Ramnani, Sakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Sixth cranial nerve palsy can occur either during or after gestation, and is often associated with hypertensive disorders of pregnancy. We report a case of a 39-year-old hypertensive primigravida with a twin pregnancy, who suddenly developed double vision in her second trimester. She was diagnosed to have isolated sixth cranial nerve palsy in her left eye. Her anterior and posterior segment examination, as well neurological imaging, were found to be entirely within normal limits. She was subsequently admitted with severe pre-eclampsia and haemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome, and managed conservatively. The prognosis is usually favorable in such cases, with the palsy resolving as the blood pressure normalizes after delivery. This case demonstrates isolated abducens nerve palsy as the first sign of pre-eclampsia at 30 weeks of gestation.